Compressive properties on the spherical-roof contoured-core cell with different amounts of diamond-shaped notches - Ma, Quanjin; Rejab, M. R. M.; Idris, Mat Sahat; Merzuki, M.N.M.; Shaoliang, Huang (IOP Publishing, 2020)
It is a challenging task to develop lightweight materials and novel structures, which offers better energy-absorbing characteristics. Therefore, it is still a significant issue to obtain secondary processing on available contoured-cores to provide a lightweight structure. This paper is aimed to investigate the effect of compressive properties on the single spherical-roof contoured-core cell with series diamond-shaped notches subjected to quasi-static compressive loading, which is referential concept on second weight reduction. The spherical-roof contoured-core panel was manufactured using a compression moulding process, and then cut to every single cell followed the diamond-shaped notch mould. It is concluded that with the number of diamond-shaped notches increasing, compressive strength and modulus generally shows the decreasing trend. Energy absorption, specific energy absorption, and peak load are also studied. In addition, the failure types of single cell units are discussed according to corresponding experimental results. It is highlighted that diamond-shaped notch cutting fabrication of core structure is a sufficient method to reduce the load concentration at the spherical-roof apex.